Association of lumbar disc prolapse with obesity in north Indian population - Ekramuddin; Shirin Jahan; Anil Kumar (Al Ameen Medical College, 2022)
Background: Lumbar disc prolapse is one of the causes of low back pain. The inner segment of the intervertebral disc bulges into and ruptures through the outer segment of the disc into the spinal canal. The disc prolapse starts as a result of lumbar disc degeneration which is an age related process influenced by mechanical and genetic factors. The present study aimed to find the association of disc prolapse with obesity, one of the risk factor, in the north Indian population. Methods: A total of 200 subjects (100 cases and 100 controls) were finally selected for this study. All the subjects were from north India. The cases were patients who came to Rama Medical College Hospital and Research Centre with complaint of low back pain and diagnosis of lumbar disc prolapse was confirmed by MRI and clinical examination. The controls were volunteers from the general population. Odds ratios with 95% confidence intervals were calculated using unconditional logistic regression analysis. Results: The risk of disc prolapse increased with the increase in weight in both sexes. In female subjects, the risk of lumbar disc prolapse increased with the increase in BMI. The highest risk of lumbar disc prolapse in male subjects was seen in overweight subjects (BMI 25-30 kg/m2) but declined with further increase in BMI. Conclusion: The present study found direct association between obesity and the lumbar disc prolapse in the north Indian population.